Rachunek zysków i strat jako narzędzie controllingu w jednostce gospodarczej - Dyduch, Alina (Profit and Loss Account as Instrument of Controlling in Enterprise, 2005)
Profit and loss account is prepared with regard to the superior principles of accountancy. Information on profit value obtained from the profit and loss account is the basis of planning it. This planning comprises not only profit, but also revenues and costs. The profit can be planned on the basis of main systems of costing, e.g. direct costing. Both in operational and strategic controlling there is a need to use information on profit value and on elements building it in the long run (strategic controlling) and in the short run (operational controlling).(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 132-138